Answer:
(-3,1)
y= 1
x= -3
Explanation:
4x-9y=-21
-4x-3y=9
solve the equation
4x=-21+9y
-4x-3y=9
substitute the value of 4x onto an equation
-1(-21+9y)-3y=9
multiply -1 to the numbers in parenthesis
-21+-9-3y=9
add -9 to 9 and put the negative on nine as a positive.
-21-3y=18
add -21 to 18 but since 21 is a negative the equation is subtraction.
-3y=-3
divide Both sides by -3
y=1
substitute the value of y into an equation
-4x-3•1=9
multiply 3 to 1
-4x-3=9
put -3 as a positive and add 3 to 9
-4x=12
divide both sides by -4
x= -3
(-3,1)